Growth Phase-Dependent Invasion of Pseudomonas aeruginosa and Its Survival within HeLa Cells - Ha, Unhwan (American Society for Microbiology, 2001)
Clinical isolates of Pseudomonas aeruginosa are classified into invasive and noninvasive (cytolytic) strains. In a noninvasive PA103 background, ExoS and ExoT have recently been shown to function as anti-internalization factors. However, these two factors seemed not to have such a function in an invasive strain PAK background. In this study, using HeLa tissue culture cells, we observed that the internalization of invasive strain PAK is dependent on its growth phases, with the stationary-phase cells internalized about 100-fold more efficiently than the exponential-phase cells. This growth phase-dependent internalization was not observed in the noninvasive PA103 strain. Further analysis of various mutant derivatives of the invasive PAK and the noninvasive PA103 strains demonstrated that ExoS or ExoT that is injected into host cells by a type III secretion machinery functions as an anti-internalization factor in both types of strains. In correlation with the growth phase-dependent internalization, the invasive strain PAK translocates much higher amount of ExoS and ExoT into HeLa cells when it is in an exponential-growth phase than when it is in a stationary-growth phase, whereas the translocation of ExoT by the noninvasive strain PA103 is consistently high regardless of the growth phases, suggesting a difference in the regulatory mechanism of type III secretion between the two types of strains. Consistent with the invasive phenotype of the parent strain, an internalized PAK derivative survived well within the HeLa cells, whereas the viability of internalized PA103 derivative was dramatically decreased and completely cleared within 48 h. These results indicate that the invasive strains of P. aeruginosa have evolved the mechanism of intracellular survival, whereas the noninvasive P. aeruginosa strains have lost or not acquired the ability to survive within the epithelial cells.